Availability and applicability of cardiac magnetic resonance imaging in diagnosis in cardiomyopathies: the Cardiomyopathy/Myocarditis registry of the EURObservational Research Programme of the ESC. (25th November 2020) - Mizia-Stec, K; Charron, P; Blanes, J.R.G; Elliott, P; Kaski, J.P; Maggioni, A.P; Tavazzi, L; Tendera, M; Wybraniec, M; Laroche, C; Caforio, A.L.P
Abstract: Background: Cardiac magnetic resonance (CMR) constitutes a gold standard in the diagnosis of cardiomyopathies. Regardless of CMR advantages, the method is time-consuming, high-cost, with limited availability in some European regions. Purpose: To assess the availability and applicability of CMR for establishing the diagnosis in different populations of patients with cardiomyopathies. Methods: Overall, 3208 adult patients with cardiomyopathy (1119 / 34.9% females; median age at diagnosis: 49.0 years): 1260 with dilated (DCM), 1739 with hypertrophic (HCM), 66 with restrictive (RCM) and 143 with arrhythmogenic right ventricular cardiomyopathy (ARVC) enrolled in EURObservational Research Programme (EORP) – Cardiomyopathy/Myocarditis Long-Term Registry were analysed. Results: CMR scan was performed as a baseline diagnostic method in 29.4% of patients; CMR was a single diagnostic method in 0.9% of patients and in 28.6% of patients CMR was used along with transthoracic echocardiography (TTE). In 67.6% of patients TTE was at the baseline the single diagnostic imaging method. Prevalence of CMR use in different cardiomyopathies was as follows: 20.6% in DCM, 33.8% in HCM, 36.4% in RCM and 51.1% in ARVC (p<0.001). Range of CMR applicability in different European regions was diverse from 0% up to 63.2%. The population with CMR use was younger, less symptomatic, with decreased prevalence of other cardiovascular risk factors and of associated cardiovascular diseases as compared to the population diagnosed without CMR scanning (p<0.001). Abnormal CMR results were present in 93.4% of patients with the highest percentage in RCM (95.8%) and HCM (94.9%) followed by DCM (91.5%) and the lowest abnormal CMR scan ratio in ARVC (87.7%) (p=0.030). The majority of CMR examinations comprised the assessment of late gadolinium enhancement (LGE, 93.3% at baseline). Presence of CMR LGE was observed in 69.3% of all patients: 59.1% in DCM, 73.8% in HCM, in 63.9% in ARVC and with the highest prevalence in RCM (83.3%) (p<0.001). Conclusion: The study reveals real-life data on the low availability and applicability of CMR in adult patients with cardiomyopathies. The analysis shows the advantages of CMR imaging but also identifies the gaps between recommendations and clinical practice. Improvement regarding access, training and reimbursement is necessary to offer CMR to cardiomyopathy patients in accordance with the ESC guidelines. Funding Acknowledgement: Type of funding source: None